Respuesta :

Step-by-step explanation:

3×‐9×-5y-2y =0-7

-6x-7y =-7

Answer:

[tex]x = \frac{9}{13} \ , \ y = - \frac{5}{13}[/tex]

Step-by-step explanation:

                         3x - 5y = 4 ----------- ( 1 )

                         9x - 2y = 7 -----------( 2 )

                 ______________________

( 1 ) x 9  =>       27x - 45y = 36   ----------------- ( 3 )

( 2) x 3 =>        27x - 6y = 21     -------------------( 4 )

                  _____________________

( 3 )  =>          27x - 45y = 36

- ( 4 ) =>         -27x + 6y = - 21

                   ____________________

( 3 ) - ( 4 ) =>     0x - 39y = 15

                            -39y = 15

                                [tex]y = \frac{15}{-39} = -\frac{5}{13}[/tex]

Substitute y in ( 1 ) :

                     [tex]3x - 5y = 4\\\\3x - ( 5 \times -\frac{5}{13}) = 4\\\\3x + \frac{25}{13} = 4\\\\3x = 4 - \frac{25}{13}\\\\3x = \frac{52 - 25}{13}\\\\3x = \frac{27}{13}\\\\x = \frac{27}{13 \times 3}\\\\x= \frac{9}{13}[/tex]                        

ACCESS MORE